Effects of Swimming on the Inflammatory and Redox Response in a Model of Allergic Asthma - Brüggemann, T. R.; Ávila, L. C. M.; Fortkamp, B.; Greiffo, F. R.; Bobinski, F.; Mazzardo-Martins, L.; Martins, D. F.; Duarte, M. M. M. F.; Dafre, A.; Santos, A. R. S.; Silva, M. D.; Souza, L. F.; Vieira, R. P.; Hizume-Kunzler, D. C. (International Journal of Sports Medicine, 2015)
In this study we hypothesized that swimming during sensitization phase could result in a preventive effect in mice with allergic asthma. Swiss mice were divided into 4 groups: Control and Swimming (non-sensitized), OVA and OVA+Swimming (sensitized). The allergic inflammation was induced by 2 intraperitoneal injections and 4 aerosol challenges using ovalbumin. Swimming sessions were performed at high intensity over 3 weeks. 48 h after the last challenge mice were euthanized. Swimming decreased OVA-increased total IgE, IL-1, IL-4, IL-5 and IL-6 levels, as well as the number of total cells, lymphocytes and eosinophils in bronchoalveolar lavage fluid, (p<0.05). Simultaneously, swimming also increased IL-10 and glutathione levels in the Swimming and OVA+Swimming groups (p<0.05). The levels of glutathione peroxidase and catalase were increased only in the Swimming group when compared to all groups (p<0.05). 21 days of swimming resulted in an attenuation of pulmonary allergic inflammation followed by an increase of glutathione levels in the OVA group. Swimming only increased the levels of glutathione peroxidase and catalase in non-sensitized mice (p<0.05). These data suggest that the pulmonary anti-inflammatory effects produced by 3 weeks of high-intensity swimming in this model of OVA-induced asthma may be, at least partly, modulated by reduced oxidative stress and increased IL-10 production.
Keywords: swimming; antioxidant system; pulmonary inflammation